Imagining imperial frontiers: Photography-as-cartography in the mapping of eastern Africa. (April 2022) - MacArthur, Julie
Abstract: This paper examines the construction of imperial landscapes in the borderlands of eastern Africa in the early twentieth century. Recent literature has emphasized the haphazard, contingent, and often hybrid nature of mapping imperial frontiers and colonial governance in eastern Africa. This paper looks at the role of photography in the mapping of the Kenya-Somali frontier through the rich photographic archive of colonial official, Sir Geoffrey Archer. Archer documented his cartographic surveys through multiple media – diaries, maps, photographs – that provide a unique lens through which to explore the role of visual culture in contestations over territoriality, mobility, and sovereignty. While this photographic archive visualized imperial frontier landscapes and documented the work of cartographic surveys, it also revealed the dependency on local intermediaries, through their labour, geographic knowledge, and spatial practices. Photography-as-cartography demonstrated both the productive work of photography and the ambivalent presence of colonized peoples in the mapping of imperial frontiers, revealing the social lives of the borderlands and capturing fugitive meanings, bodies, and landscapes. Highlights: Role of photography in imperial cartography and conquest of eastern Africa. Visualization of imperial frontiers and imaginations through photography. Role of and dependencies on local labour and intermediaries. Somali geographic knowledge and the social lives of borderlands. Sovereign gaze subverted by subaltern stowaway presences and fugitive landscapes.